Hepatic Safety of IL-17 Inhibitors in Psoriasis and Psoriatic Arthritis: A 12-Month Retrospective Cohort Evaluation Using the FIB-4 Index - Bakay, Umut; Duran, Tugba Izci; Karstarli Bakay, Ozge Sevil; Ekmekcioglu, Rahime (Dermatology Practical & Conceptual, 2026)
Introduction: Psoriasis (PsO) and psoriatic arthritis (PsA) are chronic immune-mediated diseases frequently associated with metabolic dysfunction–associated steatotic liver disease (MASLD). Interleukin-17 (IL-17) contributes to both psoriatic inflammation and hepatic fibrogenesis. However, long-term real-world data on the hepatic safety of IL-17 inhibitors remain limited.Objectives: To evaluate longitudinal changes in hepatic fibrosis risk using the Fibrosis-4 (FIB-4) index in PsO and PsA patients treated with IL-17 inhibitors and to assess concurrent trends in skin activity and liver enzymes in a dual-center, retrospective cohort.Methods: Adults with PsO ± PsA who received secukinumab or ixekizumab for ≥12 months at two tertiary centers were retrospectively analyzed. FIB-4 index, liver enzymes (AST, ALT, GGT), and Psoriasis Area and Severity Index (PASI) were assessed at baseline, 3, 6, and 12 months. Patients with chronic liver disease, hepatotoxic drug exposure, or incomplete follow-up were excluded.Results: A total of 123 patients (mean age 45.2 ± 11.7 years; 59.3% male; 79.7% with PsA) were included. Median baseline FIB-4 was 1.06 (IQR 0.84–1.32); 17.9% of patients were in the intermediate-high risk category. FIB-4 values and risk distribution remained stable over 12 months (P=0.76). Liver enzyme levels did not change significantly, and no hepatotoxic event occurred. Median PASI improved from 12.3 (IQR 7.9–18.7) to 1.1 (IQR 0.5–2.2) at month 12 (P<0.001), with 68.1% of patients achieving PASI ≤1. There was no correlation between changes in PASI and FIB-4 (ρ= -0.08; P=0.27).Conclusions: IL-17 inhibitors provided substantial clinical efficacy and stable hepatic fibrosis risk over 12 months, including among patients with intermediate-high baseline FIB-4. These findings support the hepatic safety of IL-17 blockade in psoriatic disease and highlight the importance of routine fibrosis monitoring in metabolic-risk populations.